Hemovigilance and Blood Safety: A Review: Hemovigilance and Blood Safety: A Review - Ishaq, Geer Mohamed (International Journal of Pharmaceutical & Biological Archive, 2018)
Blood transfusion has certain risks, and any unfavorable event occurring in a patient during or after transfusion, for which no other reason can be found, is called a transfusion reaction. These untoward effects vary from being relatively mild to severe and require rapid recognition and management. Transfusion services rely on transfusion reaction reporting to provide patient care and protect the blood supply. Unnecessary discontinuation of blood is a major wastage of scarce blood, as well as man, hours, and funds. Although strict procedures are applied during blood donations preparations and transfusions, errors in transfusion and infection complications still serve a problem in clinical practice. Hemovigilance is intended for the detection and analyzing all untoward effects of blood transfusion to correct their cause and prevent recurrence. In this review, we will discuss hemovigilance and transfusion-related adverse events.